Synthesis and X-ray crystallography of (1R,3aR,7aR)-1-((S)-1-((2R,5S)-5-(3-hydroxypentan-3-yl)tetrahydrofuran-2-yl)ethyl)-7a-methyloctahydro-4H-inden-4-one - Lo, Modou; Martínez, Andrea; Santalla, Hugo; Garrido, Fátima; Barry, Aliou Hamady; Gaye, Mohamed (European Journal of Chemistry, 2017)
The crystal of the title compound, C21H36O3 contains an oxolane ring, and six defined stereocenters which are unambigously established by the crystallography study. A three dimensional supramolecular architecture is ensured by hydrogen bonds from the hydroxy group which is both engaged in inter (O-H···O2) and intramolecular C-H···O-H) hydrogen bonds. Weak C-H···O=C hydrogen bonds are involved also into the consolidation of the network.